Identifikasi Pola Konfigurasi Mahasiswa Menggunakan First-Order Configural Frequency Analysis - Rafi Fitra; Nusar Hajarisman (Jurnal Riset Statistika, 2026)
Abstract. Students' academic performance is influenced by a combination of characteristics that are often difficult to identify using conventional variable-oriented statistical approaches. This study applies First-Order Configural Frequency Analysis (CFA) to examine configuration patterns in multivariate categorical data. CFA is a person-oriented statistical method designed to identify configurations of categorical variables that occur significantly more or less frequently than expected under a baseline independence model. Using a dataset of 1,690 students from the 2022 cohort at Universitas Islam Bandung, four categorical variables were analyzed: Grade Point Average (GPA) category, student satisfaction with the university, participation in competitions, and organizational involvement. The global test of independence indicates that the variables are not mutually independent at the 5% significance level. The analysis identifies several statistically significant type configurations, primarily involving low to moderate GPA combined with active participation in competitions and/or student organizations. In contrast, anti-type configurations are characterized by the joint occurrence of inactivity in both competitions and organizations together with dissatisfaction toward the university. These findings demonstrate the ability of First-Order CFA to uncover meaningful configuration patterns in categorical data that are not captured by conventional variable-oriented statistical analyses. Abstrak. Prestasi akademik mahasiswa dipengaruhi oleh kombinasi berbagai karakteristik yang sering kali sulit diidentifikasi menggunakan pendekatan statistika yang berorientasi pada variabel. Penelitian ini menerapkan First-Order Configural Frequency Analysis (CFA) untuk mengkaji pola konfigurasi pada data kategorik multivariat. CFA merupakan metode statistika berorientasi individu (person-oriented) yang dirancang untuk mengidentifikasi konfigurasi variabel kategorik yang muncul secara signifikan lebih sering atau lebih jarang dibandingkan dengan frekuensi yang diharapkan berdasarkan model independensi sebagai model dasar. Data yang dianalisis mencakup 1.690 mahasiswa Angkatan 2022 Universitas Islam Bandung, dengan empat variabel kategorik, yaitu kategori Indeks Prestasi Kumulatif (IPK), kepuasan mahasiswa terhadap universitas, keaktifan dalam lomba, dan keaktifan dalam organisasi. Hasil uji independensi global menunjukkan bahwa keempat variabel tersebut tidak saling bebas pada taraf signifikansi 5%. Analisis CFA mengidentifikasi beberapa konfigurasi bertipe type yang secara statistik signifikan, yang terutama melibatkan mahasiswa dengan IPK rendah hingga sedang yang aktif dalam lomba dan/atau organisasi. Sebaliknya, konfigurasi anti-type ditandai oleh kombinasi ketidakaktifan dalam lomba dan organisasi yang disertai dengan ketidakpuasan terhadap universitas. Temuan ini menunjukkan kemampuan First-Order CFA dalam mengungkap pola konfigurasi bermakna pada data kategorik yang tidak dapat dijelaskan secara memadai melalui pendekatan statistika konvensional yang berorientasi pada variabel.